A compact multiband printed antenna for smart‐phone applications. Issue 10 (October 2015) - Ding, Hong‐Ze; Jiao, Yong‐Chang; Ni, Tao
ABSTRACT A multiband coupled‐fed printed antenna with compact branch structure for 4G mobile phone is proposed in this letter. The antenna has a planar structure with a small board space of 15 × 29 mm2. A driven monopole strip and a coupled branch‐strip are developed on different sides of a thin FR4 substrate to produce different operation bands. The antenna can operate in octa‐bands, including GSM850, GSM900, DCS1800, PCS1900, UMTS, LTE2300, LTE2500, and WLAN, with the return losses more than 6 dB. A prototype of the proposed antenna is fabricated, and its measured results including return losses, efficiencies, and gains are presented. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:2289–2294, 2015